Profiling the diversity of the village chicken faecal microbiota using 16S rRNA gene and metagenomic sequencing data to reveal patterns of gut microbiome signatures - Nene, Mxolisi; Kunene, Nokuthula Winfred; Pierneef, Rian; Hadebe, Khanyisile (Frontiers in Microbiology, 2025)
IntroductionThe production environment of extensively raised village chickens necessitates their adaptability to low-resource systems. The gut microbiome plays a critical role in supporting this adaptability by influencing health and productivity. This study aimed to investigate the diversity and functional capacities of the faecal microbiome in village chickens from Limpopo and KwaZulu-Natal provinces of South Africa.MethodsUsing a combination of 16S rRNA gene sequencing and shotgun metagenomic sequencing technologies, we analysed 98 16S rRNA and 72 metagenomic datasets. Taxonomic profiles and functional gene annotations were derived, focusing on microbial diversity, antibiotic resistance genes (ARGs), and potential zoonotic pathogens.ResultsTaxonomic analysis showed that the predominant phyla in both provinces were Firmicutes, Bacteroidota, Proteobacteria, and Actinobacteria. At the genus level, Escherichia and Shigella were prevalent, with Escherichia coli and Shigella dysenteriae identified as major contributors to the gut microbiome. ARGs were identified, with MarA, PmrF, and AcrE detected in KwaZulu-Natal, and cpxA, mdtG, and TolA in Limpopo. These genes primarily mediate antibiotic efflux and alteration.DiscussionThe detection of zoonotic bacteria such as Escherichia coli and Streptococcus spp. highlights potential health risks to humans through the food chain, emphasizing the importance of improved household hygiene practices. This study underscores the role of the gut microbiome in village chicken health and adaptability, linking microbial diversity to production efficiency in low-resource settings. Targeted interventions and further research are crucial for mitigating zoonotic risks and enhancing sustainability in village chicken farming.